Corporate fraud exposed a comprehensive and holistic approach - Baker, H. Kent (Harold Kent), 1944-; Purda, Lynnette; Saadi, Samir (Emerald Publishing Limited, 2020)
Corporate Fraud Exposed uncovers the motivations and drivers of fraud including agency theory, executive compensation, and organizational culture. It delves into the consequences of fraud for various firm stakeholders, and its spillover effects on other corporations, the political environment, and financial market participants.